Continuous 25-yr aerosol records at coastal Antarctica: I: inter-annual variability of ionic compounds and links to climate indices - Weller, Rolf; Wagenbach, Dietmar; Legrand, Michel; Elsässer, Christoph; Tian-Kunze, Xiangshan; König-Langlo, Gert (Tellus. Series B, Chemical and physical meteorology, 2011)
The aerosol climatology at the coastal Antarctic Neumayer Station (NM) was investigated based on continuous, 25-yr long observations of biogenic sulphur components (methanesulfonate and non-sea salt sulphate), sea salt and nitrate. Although significant long-term trends could only be detected for nitrate (−3.6 ± 2.5% per year between 1983 and 1993 and +4.0 ± 3.2% per year from 1993-2007), non-harmonic periodicities between 2 and 5 yr were typical for all species. Dedicated time series analyses revealed that relations to sea ice extent and various circulation indices are weak at best or not significant. In particular, no consistent link between sea ice extent and sea salt loadings was evident suggesting only a rather local relevance of the NM sea salt record. Nevertheless, a higher Southern Annular Mode index tended to entail a lower biogenic sulphur signal. In examining the spatial uniformity of the NM findings we contrasted them to respective 17 yr records from the coastal Dumont d’Urville Station. We found similar long-term trends for nitrate, indicating an Antarctic-wide but not identifiable atmospheric signal, although any significant impact of solar activity or pollution could be ruled out. No inter-site variability on the multiannual scale was evident for the other ionic compounds.